HLA-DRB3/4/5 Matching Improves Outcome of Unrelated Hematopoietic Stem Cell Transplantation - Tsamadou, Chrysanthi; Engelhardt, Daphne; Platzbecker, Uwe; Sala, Elisa; Valerius, Thomas; Wagner-Drouet, Eva; Wulf, Gerald; Kröger, Nicolaus; Murawski, Niels; Einsele, Hermann; Schaefer-Eckart, Kerstin; Freitag, Sebastian; et al. (Frontiers in Immunology, 2021)
The HLA-DRB3/4/5 loci are closely linked to the HLA-DRB1 gene. Mismatches in these loci occur with a frequency of about 8-12% in otherwise 10/10 HLA-matched transplant pairs. There is preliminary evidence that these disparities may associate with increased acute graft versus host disease (GvHD) rates. Aim of this study was to analyze a large cohort of German patients and their donors for HLA-DRB3/4/5 compatibility and to correlate the HLA-DRB3/4/5 matching status with the outcome of unrelated hematopoietic stem cell transplantation (uHSCT). To this end 3410 patients and their respective donors were HLA-DRB3/4/5 and HLA-DPB1 typed by amplicon based next generation sequencing (NGS). All patients included received their first allogeneic transplant for malignant hematologic diseases between 2000 and 2014. Mismatches in the antigen recognition domain (ARD) of HLA-DRB3/4/5 genes were correlated with clinical outcome. HLA-DRB3/4/5 incompatibility was seen in 12.5% (n=296) and 17.8% (n=185) of the 10/10 and 9/10 HLA-matched cases, respectively. HLA-DRB3/4/5 mismatches in the ARD associated with a worse overall survival (OS) as shown in univariate (5-year OS: 46.1% vs. 39.8%, log-rank p=0.038) and multivariate analyses (HR 1.25, CI 1.02-1.54, p=0.034) in the otherwise 10/10 HLA matched subgroup. The worse outcome was mainly driven by a significantly higher non-relapse mortality (HR 1.35, CI 1.05-1.73, p=0.017). In the 9/10 HLA-matched cases the effect was not statistically significant. Our study results suggest that mismatches within the ARD of HLA-DRB3/4/5 genes significantly impact outcome of otherwise fully matched uHSCT and support their consideration upon donor selection in the future.